Everyday pornography - Boyle, Karen (Routledge, 2010)
Drawing on the experiences of activists alongside academics, 'Everyday Pornography' offers the opportunity to explore the intellectual & political challenges of anti-pornography feminism & consider its relevance for contemporary academic debate
https://katalog.adlr.link/Record/0-617738912